Oral insulin delivery using artificial peptide - Adikane, V. Harshavardhan (Indian Journal of Biochemistry & Biophysics, 2021)
The daily multiple insulin injection is the line of treatment for diabetes mellitus. As the oral insulin delivery mimics, the physiology of endogenous insulin secreted by pancreas. Recently, the search for suitable carrier to develop oral insulin delivery has been intensified. However, the carrier toxicity and very less bioavailability of insulin remains the major problem in the development of oral insulin delivery. Preparation of a non-covalent insulin-peptide complex using different peptide made of 16 to 20 L-amino acids studied to overcome the problem. The in vitro testing of insulin-peptide complex showed significant stability against the proteolytic enzyme. Whereas, in in vivo testing, the presence of 10-41% insulin in blood plasma observed after 30 to 60 min oral feeding of insulin-peptide complex. Results indicated that the peptide which showed moderate protection against pepsin and minor protection against trypsin and chymotrypsin has an important role in enhancing oral insulin bioavailability. However, the peptide which showed higher protection against trypsin and no protection against pepsin could not achieve significant oral insulin bioavailability.
Keywords: Bioavailability; Carrier toxicity; Insulin-peptide complex; Oral insulin delivery; Proteolytic enzyme resistance